Design and construction of a lab-scale briquette press frame structure - Tony Siagian; Muhammad Asyfa; Tengku Jukdin Saktisahdan; Intan Zahar; Ali Hasimi Pane (Jurnal VORTEKS, 2026)
The increasing global energy demand and high dependence on fossil fuels have encouraged the development of biomass-based alternative energy through briquetting technology. However, research on the structural frame design of laboratory-scale briquette press machines remains limited, particularly regarding structural strength validation using engineering analysis approaches. This study aims to design and analyze the structural strength of a hydraulic-based briquette press frame for laboratory applications. The research gap lies in the limited integration of structural analysis, safety factor evaluation, and frame optimization in small-scale briquette machines. The novelty of this study is the development of an ASTM A36-based frame using an integrative approach involving Computer Aided Design (CAD), stress analysis, buckling, and fatigue evaluation under pressure variations of 1000–1600 psi. The research method employed an experimental design and build approach combined with structural simulations and hydraulic pressure testing. The results showed that the maximum stress of 17.24 MPa remained far below the yield strength of ASTM A36 material, with a fatigue safety factor of 14.5, indicating that the structure is safe, elastic, and suitable for laboratory-scale biomass research applications